MicroRNA-29c Acting on FOS Plays a Significant Role in Nonalcoholic Steatohepatitis Through the Interleukin-17 Signaling Pathway - Cai, Chao; Chen, Da-Zhi; Tu, Han-Xiao; Chen, Wen-Kai; Ge, Li-Chao; Fu, Tian-Tian; Tao, Ying; Ye, Sha-Sha; Li, Ji; Lin, Zhuo; Wang, Xiao-Dong; Xu, Lan-Man; et al. (Frontiers in Physiology, 2021)
Nonalcoholic fatty liver disease, which is the most common hepatic disease in western countries is more ubiquitous in Asian countries. In our study, we found that TH17/Treg cells were out of balance in animal models. We are interested in the mechanism of TH17/Treg cell imbalance in nonalcoholic fatty liver mice. Therefore, we conducted a joint bioinformatics analysis for further research. Common gene sequencing analysis was based on one trial from one sequencing platform, proceeding gene expression analysis and enrichment analysis only on it. We compared different sequencing results from different trials on different sequencing platforms and used the intersection of their results to perform joint analysis. We used a bioinformatics analysis method to perform enrichment analysis, map interaction network, and predict potential microRNA sites. Animal experiments were also designed to validate the results of the data analysis by qPCR and Western blotting. The results revealed 8 co-existing differentially expressed genes (DEGs) and 7 hinge genes. Identifying DEGs may influence nonalcoholic steatosis hepatitis through the IL-17 pathway. We found that microRNA-29c interacts with FOS and IGFBP1. PCR showed not only FOS but also microRNA-29c expression in NASH mice. WB results showed the same trend in the level of protein FOS. Based on these results, we suggest that microRNA-29c acting on FOS plays an important role in NASH patients via the IL-17 signaling pathway, which also regulates TH17/Treg cells.